The landing obligation calls for a more flexible technical gear regulation in EU waters – Greater industry involvement could support development of gear modifications. (January 2019) - Eliasen, Søren Qvist; Feekings, Jordan; Krag, Ludvig; Veiga-Malta, Tiago; Mortensen, Lars O.; Ulrich, Clara
Abstract: Rigid fisheries management frameworks often leave fishers with limited possibilities and incentives to adjust the selectivity of their gears to the specific fishing conditions. Implementation of the landing obligation in European fisheries emphasizes fishers need to flexibility in which gear to use to be able to match the selectivity of the gear to the quota available. How fishers can play an important role in facilitating a more regionalised and flexible technical regulation by actively participating in the development of gears and contributing to the scientific documentation of their selectivity is discussed. Perspectives in the proposed technical regulation for EU fisheries and the regionalisation in the 2013 Common Fisheries Policy are discussed based on an analysis of the current EU technical regulation. Then is discussed a new pathway to address the problem, currently being trialled in Danish fisheries. Throughout the article, three themes are discussed: Identifying gear needs, development and testing of gear with fishers as central actors; how the selectivity of the gear should be documented; and opportunities for faster evaluation of new gear, following the regionalisation of the technical measure regulation. The paper concludes that a more flexible system of gear development and evaluation is possible by a) involvement of fishers in proposing gear adjustments, self-sampling and documenting results following scientific protocols and evaluation, testing a range of designs before scientific testing, and b) open for faster approval of gear use under a regionalised technical regulation regime with yearly adjustments of management plans containing the technical regulation. Highlights: The landing obligation requires the fishers to have gear flexibility to match the selectivity of gear to the available quota. Regionalisation of management plans opens for faster evaluation and decision on proposed new selective gear variations. Scientific support to fishers ideas speed up identification of promising gear design for scientific tests at a low-cost. Fishers involvement depend on processes for gear development and political implementation of successful selective gears. The debated EU Technical measures regulation might prove gear flexibility and fast tracking processes and fisher involving.